Liver transplantation and comprehensive rehabilitation in the reversal of hepatic myelopathy: a case report - Mingyue Liu; Rongping Wang; Wenwen Zhou; Chunyan Tian; Qian Wang; Qin Zhang; Shasha Jin; Liang Wu (Frontiers in Medicine)
Hepatic myelopathy (HM) is a rare complication of end-stage chronic liver disease, primarily presenting as symmetrical lower limb weakness that progresses to spastic paralysis without sensory or sphincter dysfunction. We report a case of decompensated cirrhosis associated with hepatitis B virus and HM. The patient showed significant recovery after liver transplantation (LT) and comprehensive rehabilitation training. We summarize the patient’s clinical characteristics post-diagnosis and the assessment outcomes following integrated treatment.